"Restauro e Reabilitação da Torre do Capitão", "Reabilitação e Ampliação do Centro de Dia da Misericórdia de Santa Cruz", "Centro Cultural e Paroquial de Santa Cruz", "Reabilitação, Ampliação e Museografia do Solar do Ribeirinho para instalação de Arquivo Histórico Municipal", "Reabilitação e Ampliação do Centro de Dia do Vale Formoso", "Reabilitação, Restauro e Ampliação do Convento de São Bernardino" - Mestre, Victor; Aleixo, Sofia (Delegação da Madeira da Ordem dos Arquitectos Secção Regional Sul, 2017)
Selecção de projectos no âmbito do Roteiro de Arquitectura da Madeira promovido pela Delegação da Madeira da OASRS
"Restoration and reabilitation of Torre do Capitão", "Rehabilitation and extension of the Elderly Home of Santa Cruz", "Community and Parish Hall of Santa Cruz", "Rehabilitation, extension and adaptadion of Solar do Ribeirinho to house the Municipal Historical Archive", "Rehabilitation and extension of Vale Formoso elderly day care and residential care home", "Rehabilitation, restoration and extension of São Bernardino Convent"